How is suicide risk assessed in healthcare settings in the UK? A systematic scoping review. - Sophia E Fedorowicz; Robert C Dempsey; Naomi Ellis; Elliott Phillips; Christopher Gidlow (PLoS ONE)
A high proportion of people contact healthcare services in the 12 months prior to death by suicide. Identifying people at high-risk for suicide is therefore a key concern for healthcare services. Whilst there is extensive research on the validity and reliability of suicide risk assessment tools, there remains a lack of understanding of how suicide risk assessments are conducted by healthcare staff in practice. This scoping review examined the literature on how suicide risk assessments are conducted and experienced by healthcare practitioners, patients, carers, relatives, and friends of people who have died by suicide in the UK. Literature searches were conducted on key databases using a pre-defined search strategy pre-registered with the Open Science Framework and following the PRISMA extension for scoping reviews guidelines. Eligible for inclusion were original research, written in English, exploring how suicide risk is assessed in the UK, related to administering or undergoing risk assessment for suicide, key concepts relating to those experiences, or directly exploring the experiences of administering or undergoing assessment. Eighteen studies were included in the final sample. Information was charted including study setting and design, sampling strategy, sample characteristics, and findings. A narrative account of the literature is provided. There was considerable variation regarding how suicide risk assessments are conducted in practice. There was evidence of a lack of risk assessment training, low awareness of suicide prevention guidance, and a lack of evidence relating to patient perspectives of suicide risk assessments. Increased inclusion of patient perspectives of suicide risk assessment is needed to gain understanding of how the process can be improved. Limited time and difficulty in starting an open discussion about suicide with patients were noted as barriers to successful assessment. Implications for practice are discussed.